Acoustofluidics‐Assisted Fluorescence‐SERS Bimodal Biosensors. Issue 48 (10th November 2020) - Hao, Nanjing; Pei, Zhichao; Liu, Pengzhan; Bachman, Hunter; Naquin, Ty Downing; Zhang, Peiran; Zhang, Jinxin; Shen, Liang; Yang, Shujie; Yang, Kaichun; Zhao, Shuaiguo; Huang, Tony Jun
Abstract: Acoustofluidics, the fusion of acoustics and microfluidic techniques, has recently seen increased research attention across multiple disciplines due in part to its capabilities in contactless, biocompatible, and precise manipulation of micro‐/nano‐objects. Herein, a bimodal signal amplification platform which relies on acoustofluidics‐induced enrichment of nanoparticles is introduced. The dual‐function biosensor can perform sensitive immunofluorescent or surface‐enhanced Raman spectroscopy (SERS) detection. The platform functions by using surface acoustic waves to concentrate nanoparticles at either the center or perimeter of a glass capillary; the concentration location is adjusted simply by varying the input frequency. The immunofluorescence assay is achieved by concentrating fluorescent analytes and functionalized nanoparticles at the center of the microchannel, thereby improving the visibility of the fluorescent output. By modifying the inner wall of the glass capillary with plasmonic Ag nanoparticle‐deposited ZnO nanorod arrays and focusing analytes toward the perimeter of the microchannel, SERS sensing using the same device setup is achieved. Nanosized exosomes are used as a proof‐of‐concept to validate the performance of the acoustofluidic bimodal biosensor. With its sample‐enrichment functionality, bimodal sensing, short processing time, and minute sample consumption, the acoustofluidic chip holds great potential for the development of lab‐on‐a‐chip based analysis systems in many real‐world applications. Abstract : Acoustofluidics‐assisted signal amplification platform is introduced to develop bimodal immunofluorescent and surface‐enhanced Raman spectroscop biosensors. The platform functions by using surface acoustic waves to concentrate the target of interest at either the center or perimeter of a glass capillary. Nanosized exosomes are used as a proof‐of‐concept to validate the performance of the acoustofluidic bimodal biosensor.